2001
DOI: 10.1002/1099-0690(200101)2001:2<311::aid-ejoc311>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of the Cation Affinity of Artificial Receptors Based on Cyclic Peptides by Intramolecular Conformational Control

Abstract: A series of cyclic hexapeptides consisting of alternating 4-substituted 3-aminobenzoic acid units (R = CH 3 , Cl, CH 2 OCH 3 , OCH 3 , COOCH 3 ) and residues of the natural amino acid proline has been prepared and their ion affinities have been investigated. Whereas the unsubstituted parent compound (R = H) is able to bind cations through cation−π interactions with the aromatic subunits, as well as anions through hydrogen bonding with the peptide NH groups, the introduction of substituents at the 4-positions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…164) that was able to bind ammonium ions with stability constants between 11000 and 42000 M −1 in chloroform. The series of cyclic hexapeptides contains different 4-substituted 3-aminobenzoic acid units (R = CH 3 , Cl, CH 2 OCH 3 , OCH 3 , COOCH 3 ) [746]. The authors demonstrated that cyclic peptides 233 bind a variety of ammonium iodide salts with positive co-operativity in CDCl 3 .…”
Section: Reviewmentioning
confidence: 99%
“…164) that was able to bind ammonium ions with stability constants between 11000 and 42000 M −1 in chloroform. The series of cyclic hexapeptides contains different 4-substituted 3-aminobenzoic acid units (R = CH 3 , Cl, CH 2 OCH 3 , OCH 3 , COOCH 3 ) [746]. The authors demonstrated that cyclic peptides 233 bind a variety of ammonium iodide salts with positive co-operativity in CDCl 3 .…”
Section: Reviewmentioning
confidence: 99%
“…Finally, the protected PROTACs were deprotected using method V to yield PROTACs (1g, 1h, 1l and 1p) shown in scheme 5. The two starting materials 4-(2-methoxy-2-oxoethoxy)benzoic acid (21) [67] and benzyl 3-amino-4-chlorobenzoate (22) which were prepared as previously described [68], were reacted together using method IIIC to afford benzyl 4-chloro-3-[4-(2methoxy-2-oxoethoxy)benzamido]benzoate (23). Deprotection of the benzyl ester was achieved using method V, and the resulted acid was reacted with O- Finally, the protected HDAC ligand was reacted with E3 ligase-linker-NH 2 conjugate (53) following method IIIA to yield the protected PROTAC which was deprotected to yield PROTAC (1i) using method VII.…”
Section: Characterization Data Of Thementioning
confidence: 99%
“…Finally, the protected PROTACs were deprotected using method V to yield PROTACs (1g, 1h, 1l and 1p) shown in scheme 5. The two starting materials 4-(2-methoxy-2-oxoethoxy)benzoic acid (21) [68] and benzyl 3-amino-4-chlorobenzoate (22) which were prepared as previously described [69], were reacted together using method IIIC to afford benzyl 4-chloro-3-[4-(2methoxy-2-oxoethoxy)benzamido]benzoate (23). Deprotection of the benzyl ester was achieved using method V, and the resulted acid was reacted with O- Finally, the protected HDAC ligand was reacted with E3 ligase-linker-NH 2 conjugate (53) following method IIIA to yield the protected PROTAC which was deprotected to yield PROTAC (1i) using method VII.…”
Section: Yl)amino)octanamido)benzamido)-n-hydroxy-4-methoxybenzamide ...mentioning
confidence: 99%